2011
DOI: 10.12968/bjon.2011.20.4.220
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of the Distress Thermometer: a review

Abstract: The Distress Thermometer (DT) is a well validated screening tool, demonstrably sensitive and reasonably specific to the construct of distress in cancer. Its brevity makes it ideal to incorporate into a system of distress management. To ascertain how far this idea has been developed in practice, and to support future research, a literature review was undertaken. Medline, CINAHL, PsycINFO, Embase, ASSIA, British Nursing Index, AMED, CCTR, and HMIC were systematically searched. Forty studies were reviewed that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 53 publications
0
71
1
1
Order By: Relevance
“…Studies of the DT with cancer patients, rather than longterm survivors, have reported favorably on its psychometric properties when compared to more conventional psychological checklist measures and generally concluded that it is a clinically useful screening measure (see Snowden et al [23] for review). Several previous studies in cancer patients have reported much higher sensitivities for the DT than what we found here (e.g., 80%) [12], with even higher sensitivity being reported in a study of cancer patients' caregivers [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the DT with cancer patients, rather than longterm survivors, have reported favorably on its psychometric properties when compared to more conventional psychological checklist measures and generally concluded that it is a clinically useful screening measure (see Snowden et al [23] for review). Several previous studies in cancer patients have reported much higher sensitivities for the DT than what we found here (e.g., 80%) [12], with even higher sensitivity being reported in a study of cancer patients' caregivers [13].…”
Section: Discussionmentioning
confidence: 99%
“…The DT is a widely used and extensively validated screening instrument to assess distress caused by specific health conditions (Snowden et al, 2011). The recommended cut-off indicating clinically relevant levels of global distress is a score of 4 (Snowden et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The recommended cut-off indicating clinically relevant levels of global distress is a score of 4 (Snowden et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…We prospectively collected the following data: Palliative Performance Status (PPS) 32 and Palliative Prognostic Index (PPI) 33 on admission; daily Edmonton Symptom Assessment Score (ESAS) [34][35][36] and distress score 37 ; documentation of disciplines considered essential for patients to see; date family meeting achieved, likely outcome (on admission) and patient, family and staff satisfaction levels.…”
Section: Data Collectionmentioning
confidence: 99%